Hidden depths in the local Universe: the Stellar Stream Legacy Survey - Martínez-Delgado, David; Cooper, Andrew P.; Román, Javier; Pillepich, Annalisa; Erkal, Denis; Pearson, Sarah; Moustakas, John; Laporte, Chervin F. P.; Laine, Seppo; Akhlaghi, Mohammad; Lang, Dustin; Makarov, Dmitry; et al. (Astronomy and astrophysics, 2023)
Context: Mergers and tidal interactions between massive galaxies and their dwarf satellites are a fundamental prediction of the Lambda-cold dark matter cosmology. These events are thought to provide important observational diagnostics of non-linear structure formation. Stellar streams in the Milky Way and Andromeda are spectacular evidence for ongoing satellite disruption. However, constructing a statistically meaningful sample of tidal streams beyond the Local Group has proven a daunting observational challenge, and the full potential for deepening our understanding of galaxy assembly using stellar streams has yet to be realised.Aims: Here we introduce the Stellar Stream Legacy Survey, a systematic imaging survey of tidal features associated with dwarf galaxy accretion around a sample of ∼3100 nearby galaxies within z ∼ 0.02, including about 940 Milky Way analogues. Methods: Our survey exploits public deep imaging data from the DESI Legacy Imaging Surveys, which reach surface brightness as faint as ∼29 mag arcsec−2 in the r band. As a proof of concept of our survey, we report the detection and broad-band photometry of 24 new stellar streams in the local Universe. Results: We discuss how these observations can yield new constraints on galaxy formation theory through comparison to mock observations from cosmological galaxy simulations. These tests will probe the present-day mass assembly rate of galaxies, the stellar populations and orbits of satellites, the growth of stellar halos, and the resilience of stellar disks to satellite bombardment.